The Influence of Internal Control Quality on Corporate Financial Performance: An Empirical Analysis based on Panel Quantile Regression Model - Xu , Meng; Loang, Ooi Kok (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
This study delves into the relationship between internal control quality and the financial performance of Chinese-listed corporations. Employing a distinctive research approach featuring panel quantile regression, this study meticulously examines data spanning the period from 2011 to 2020, encompassing 953 Chinese-listed entities. The analysis, in comparison to conventional methods such as ordinary least squares (OLS) regression and fixed-effects models, consistently reveals a robust and statistically significant positive correlation between internal control quality and corporate financial performance. Notably, the findings of the panel quantile regression bring to the forefront a nuanced perspective, elucidating an enhancing effect of internal control quality on Return on Assets. Nevertheless, this effect diminishes as one ascends the quantile distribution, elucidating varying degrees of influence contingent upon the internal control quality spectrum. These findings underscore the pivotal role of effective internal control systems in augmenting financial performance, with implications for corporate governance. Furthermore, this research underscores the evolving nature of internal control frameworks, particularly in the context of digitalization, thus delineating an imperative area for prospective scholarly exploration.